2015
DOI: 10.1016/j.rhm.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, sexual health, and human rights among women who have sex with women in Lesotho

Abstract: In recent years, gender and sexual minorities have become increasingly visible across sub-Saharan Africa, marking both the progression and violation of their human rights. Using data from a study with sexual minorities in Lesotho, this analysis leveraged the social ecological model to examine relationships between stigma, human rights, and sexual health among women who have sex with women in Lesotho. A community-based participatory approach was used for the mixed-method, cross-sectional study. A total of 250 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 25 publications
4
32
0
11
Order By: Relevance
“…Recently, the link between human rights violations and HIV vulnerability was confirmed in a sample of LB women in Africa 6 . One relevant issue that maximizes the risk of HIV in LB women is the figures of sexual harassments reported by them.…”
Section: Key Topics In Hiv Prevention For Lb Womenmentioning
confidence: 90%
See 3 more Smart Citations
“…Recently, the link between human rights violations and HIV vulnerability was confirmed in a sample of LB women in Africa 6 . One relevant issue that maximizes the risk of HIV in LB women is the figures of sexual harassments reported by them.…”
Section: Key Topics In Hiv Prevention For Lb Womenmentioning
confidence: 90%
“…Few studies conducted in the population have revealed that LB women feel that health workers do not meet their needs; prefer to hide their sexual orientation in health services out of fear or services are often denied 6,16,39 . This situation may delay the detection of possible irregularities and treatment on time for this population.…”
Section: Key Topics In Hiv Prevention For Lb Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…Poteat et al, study of women who have sex with women (WSW); in Lesotho reports, 22.5% of women were afraid to seek health care due to discrimination, with 23% of women reporting health care services did not meet their needs. Disclosure of their sexual orientation to health care workers was also associated with being 8.5 times more likely to lose employment.…”
Section: Lgb Human Rights and Healthmentioning
confidence: 99%